The miRNA Interactome in Metabolic Homeostasis. (December 2015) - Hartig, Sean M.; Hamilton, Mark P.; Bader, David A.; McGuire, Sean E.
Abstract : Global expression analyses demonstrate that alterations in miRNA levels correlate with various metabolic diseases. miRNAs regulate central metabolic pathways and thus play vital roles in maintaining organismal energy balance and metabolic homeostasis. Here we highlight novel sequencing technologies used to comprehensively define the target spectrum of miRNAs in metabolic disease that complement recent literature reporting physiologic roles for miRNAs in the regulation of glucose and lipid metabolism in peripheral tissues of animal models of metabolic dysfunction. These emerging technologies help decipher the complexity of the miRNA interactome and enrich our understanding of how miRNAs mediate physiologic effects by targeting a spectrum of gene transcripts simultaneously. miRNA-based therapeutics emerge as a viable strategy for treating metabolic diseases. Trends: miRNAs regulate target mRNA expression by inducing mRNA degradation or translational inhibition. miRNAs mediate adipocyte differentiation, control beta cell mass and insulin secretion, and co-target multiple nodes of the insulin signaling pathway to globally promote or suppress diabetic phenotypes in adipose tissue, pancreas, and liver. Emerging genomic and sequencing technologies allow the definition of global miRNA–mRNA interactions that underpin metabolic regulation. Currently, most miRNAs have only a few well-characterized targets, but they are likely to work in complex, overlapping signaling networks that target many genes in the same pathway. Manipulation of antidiabetic miRNAs in vivo improves insulin sensitivity, suggesting that miRNA-based therapeutics may represent a viable strategy for treating metabolic diseases.